1988
DOI: 10.1520/jfs12578j
|View full text |Cite
|
Sign up to set email alerts
|

Color Matching Within a Fiber Data Collection

Abstract: The fiber data collection in use in the Home Office Forensic Science Service uses complementary chromaticity coordinates as a method of color description. Color variation within samples is represented by an elliptical error region around the mean chromaticity point of the sample. For searching this collection, a method of matching single colors to the collection ellipses has been assessed. However, the necessary calculations are complex, so a number of simpler alternatives has been investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…55,57 Some spectrometers enable the measurement of spectra in the 240 -760 nm range, and even 190 -900 nm. They can be adapted to the recording of fluorescent spectra.…”
Section: Spectral Analysis Using Ultraviolet Radiation and Fluorescencementioning
confidence: 99%
“…55,57 Some spectrometers enable the measurement of spectra in the 240 -760 nm range, and even 190 -900 nm. They can be adapted to the recording of fluorescent spectra.…”
Section: Spectral Analysis Using Ultraviolet Radiation and Fluorescencementioning
confidence: 99%
“…Results have shown that the ratio of fibers shed from a fabric of mixed fiber types is different from the actual content of the fabric (489). A method of matching single-colored fibers to a fiber collection using complementary chromaticity coordinates as a method of color description has been discussed (490). Undyed fiber substrate, instrumental error, delustrant level, and fiber shape have been investigated as factors causing variation in complementary chromaticity coordinates for color coding single fibers (491).…”
Section: Forensic Biochemistrymentioning
confidence: 99%
“…Some attempts have been made to use CIE coordinates in forensic science; some examiners have used the so-called Complementary Chromaticity Coordinates (CCC) [17][18][19][20], but nowadays in the field of textiles the CIE and CIEL ⁄ a ⁄ b ⁄ system are widely accepted [21,22].…”
mentioning
confidence: 99%